1999
DOI: 10.1128/jb.181.2.681-684.1999
|View full text |Cite
|
Sign up to set email alerts
|

Control of Herbaspirillum seropedicae NifA Activity by Ammonium Ions and Oxygen

Abstract: The activity of a truncated form of Herbaspirillum seropedicae NifA in different genetic backgrounds showed that its regulatory domain is involved in nitrogen control but not in O2 sensitivity or Fe dependence. The model for nitrogen control involving PII could thus apply to the proteobacteria at large. NifA may have a role in controlling ADP-ribosylation of nitrogenase inAzospirillum brasilense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
47
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 28 publications
7
47
0
Order By: Relevance
“…On the other hand, nifH expression was not inhibited by ammonia. This result also agrees with the previous observation [23] that the N-terminal domain of H. seropedicae NifA is involved in ammonia-sensing. The N-terminal domain of the NifA protein may interact with a nitrogen-sensing protein or signal molecule which, in turn, controls the interaction between the central domain and the RNA polymerase.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, nifH expression was not inhibited by ammonia. This result also agrees with the previous observation [23] that the N-terminal domain of H. seropedicae NifA is involved in ammonia-sensing. The N-terminal domain of the NifA protein may interact with a nitrogen-sensing protein or signal molecule which, in turn, controls the interaction between the central domain and the RNA polymerase.…”
Section: Resultssupporting
confidence: 93%
“…SDS-PAGE analysis con¢rmed the expression of the proteins in all conditions tested (not shown). Promoter activation as revealed by L-galactosidase activity was detected only when cells were induced under a nitrogen gas phase, con¢rming the oxygen-sensitivity of H. seropedicae NifA [23]. These results are also consistent with the hypothesis that the oxygen-sensitivity does not involve the N-terminal domain of NifA but rather the central domain and the ID linker, probably involving the putative metal-binding and redox status-sensing cysteine motif, Cys-X II -Cys-X IW -Cys-X R -Cys [6].…”
Section: Resultsmentioning
confidence: 76%
“…Hence, the interaction of the N-terminal domain of H. seropedicae is speci¢c inasmuch that did not interfere with the ATPase activity of the homologous NtrC, but the A. vinelandii NifA protein has su¤cient similarity (42%) to allow negative interaction. The observation that the N-terminal domain negatively controls the NifA activity is in agreement with previous in vivo results showing that when the N-terminal domain was expressed at a higher level, the N-truncated NifA was transcriptionally inactive [19] and that may also explain why the full length form of NifA was inactive in E. coli [13].…”
Section: Resultssupporting
confidence: 92%
“…2A). This is in agreement with in vivo data, which indicated that the H. seropedicae protein is thermostable [13]. The ATPase activity of the N-truncated protein was stimulated by the addition of the H. seropedicae nifB promoter (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The mechanism involved in this control is not known. Souza et al [30] observed that the activity of a H. seropedicae N-terminal domain-truncated NifA (DNTD) was independent of ammonium levels, suggesting that the N-terminal domain (NTD) plays a role in the control of NifA activity by ammonium. Arsene et al [3] made a similar observation in A. brasilense and suggested that PII-UMP may interact with the NTD of NifA to change its activity.…”
mentioning
confidence: 99%